The recommended dosage regimen for caspofungin in patients with higher body weight or hypoalbuminaemia will result in low exposure: Five years of data based on a population pharmacokinetic model and Monte-Carlo simulations - Yang, Qianting; Zhang, Tao; Zhang, Ying; Sun, Dan; Zheng, Xiaowei; Du, Qian; Wang, Xue; Cheng, Xiaoliang; Xing, Jianfeng; Dong, Yalin (Frontiers in Pharmacology, 2022)
Background: To develop a population pharmacokinetic (PPK) model for caspofungin, identify parameters influencing caspofungin pharmacokinetics, and assess the required probability of target attainment (PTA) and cumulative fraction of response (CFR) for various dosing regimens of caspofungin in all patients and intensive care unit (ICU)-subgroup patients. Method: The general PPK model was developed based on data sets from all patients (299 patients). A ICU-subgroup PPK model based on data sets from 136 patients was then analyzed. The effects of demographics, clinical data, laboratory data, and concomitant medications were tested. Monte-Carlo simulations (MCS) were used to evaluate the effectiveness of different caspofungin dosage regimens. Results: One-compartment model best described the data of all patients and ICU patients. Clearances (CL) were 0.32 L/h and 0.40 L/h and volumes of distribution (V) were 13.31 L and 10.20 L for the general and ICU-subgroup PPK models, respectively. In the general model, CL and V were significantly associated with albumin (ALB) concentration and body weight (WT). In the ICU-subgroup model, CL was associated with WT. The simulated exposure in ICU patients was lower than that in all patients (P < 0.05). MCS indicated that higher caspofungin maintenance doses of 70–150 mg may achieve target CFR of >90% for patients with higher WT (>70 kg) or with C. albicans or C. parapsilosis infections, and especially for ICU patients with hypoalbuminaemia. Conclusion: The PPK model and MCS presented in the study demonstrated that the recommended dosage regimen for caspofungin in patients with higher body weight or hypoalbuminaemia will result in low exposure.